2015
DOI: 10.1111/1365-2745.12492
|View full text |Cite
|
Sign up to set email alerts
|

Breaking and remaking a seed and seed predator interaction in the introduced range of Scotch Broom (Cytisus scoparius) in New Zealand

Abstract: Summary Introduced plants may initially experience enemy release, but some of those interactions may be reinstated through biological control. These cases provide opportunities to explore the dynamics of broken and remade consumer–resource interactions. The European shrub broom (Cytisus scoparius) was introduced to New Zealand without a specialist seed predator (Bruchidius villosus) until a biological control programme reinstated this interaction in 1988. Broom produces substantially larger seeds throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Biological control presents a unique opportunity to examine the potential of introduced organisms to rapidly respond to selection. Following a period of refuge from specialist natural enemies (Keane & Crawley, ), an invasive species is hypothesized to face strong selection when re‐associated with a key antagonist that is itself likely to have few natural enemies or competitors (Müller‐Schärer et al ., ; Rapo et al ., ; Seastedt, ; Paynter et al ., ). In a rare test of this hypothesis, we found that Lythrum from populations that had the longest (approx.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Biological control presents a unique opportunity to examine the potential of introduced organisms to rapidly respond to selection. Following a period of refuge from specialist natural enemies (Keane & Crawley, ), an invasive species is hypothesized to face strong selection when re‐associated with a key antagonist that is itself likely to have few natural enemies or competitors (Müller‐Schärer et al ., ; Rapo et al ., ; Seastedt, ; Paynter et al ., ). In a rare test of this hypothesis, we found that Lythrum from populations that had the longest (approx.…”
Section: Discussionmentioning
confidence: 97%
“…The potential for an invasive species to evolve in response to pressure exerted by biological control has been largely overlooked in evolutionary and applied ecology, with a very limited number of empirical studies (Rapo et al ., ; Paynter et al ., ) in spite of the existence of multidecadal biocontrol programmes for many exotics. Our findings suggest that rapid evolutionary change among populations exposed to biocontrol can occur over very short timescales and involve diverse aspects of the plant's phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to 1969, C. solstitialis in North America did not experience any feeding damage within its capitula [ 6 , 25 ]. Observations in other seed-herbivore systems show that following release of a seed predator, seed size can decline [ 26 ]. The results from this study uniquely document C. solstitialis and E. villosus early in the biological control program and provide baseline data with which to compare later observations.…”
Section: Introductionmentioning
confidence: 99%